Coronary endothelial function assessment using self‐gated cardiac cine MRI and k‐t sparse SENSE. Issue 5 (24th November 2015) - Yerly, Jérôme; Ginami, Giulia; Nordio, Giovanna; Coristine, Andrew J.; Coppo, Simone; Monney, Pierre; Stuber, Matthias
Abstract : Purpose: Electrocardiogram (ECG)‐gated cine MRI, paired with isometric handgrip exercise, can be used to accurately, reproducibly, and noninvasively measure coronary endothelial function (CEF). Obtaining a reliable ECG signal at higher field strengths, however, can be challenging due to rapid gradient switching and an increased heart rate under stress. To address these limitations, we present a self‐gated cardiac cine MRI framework for CEF measurements that operates without ECG signal. Methods: Cross‐sectional slices of the right coronary artery (RCA) were acquired using a two‐dimensional golden angle radial trajectory. This sampling approach, combined with the k ‐ t sparse SENSE algorithm, allows for the reconstruction of both real‐time images for self‐gating signal calculations and retrospectively reordered self‐gated cine images. CEF measurements were quantitatively compared using both the self‐gated and the standard ECG‐gated approach. Results: Self‐gated cine images with high‐quality, temporal, and spatial resolution were reconstructed for 18 healthy volunteers. CEF as measured in self‐gated images was in good agreement ( R 2  = 0.60) with that measured by its standard ECG‐gated counterpart. Conclusion: High spatial and temporal resolution cross‐sectional cine images of the RCA can be obtained without ECG signal. The coronary vasomotor response to handgrip exercise compares favorably with that obtained with the standard ECG‐gated method. Magn Reson Med 76:1443–1454, 2015. © 2015 International Society for Magnetic Resonance in Medicine